2019
DOI: 10.1093/ofid/ofz363
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of United States–Based Infectious Diseases Physicians on Outpatient Parenteral Antimicrobial Therapy Practice

Abstract: Background Although outpatient parenteral antimicrobial therapy (OPAT) is generally considered safe, patients are at risk for complications and thus require close monitoring. The purpose of this study is to determine how OPAT programs are structured and how United States–based infectious diseases (ID) physicians perceive barriers to safe OPAT care. Methods We queried members of the Emerging Infections Network (EIN) between No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…This strategy requires close patient follow‐up and monitoring of laboratory results to ensure safe and effective care. In addition, this approach requires a high level of coordination between hospitals, outpatient infusion facilities, and multidisciplinary coordination between clinicians, nurses, billing staff, and case management 7 . However, there are several barriers intrinsic to OPAT that compromise its safety and efficacy, thereby preventing the use of OPAT as a transition strategy.…”
Section: Barriers To Traditional Transition Strategiesmentioning
confidence: 99%
“…This strategy requires close patient follow‐up and monitoring of laboratory results to ensure safe and effective care. In addition, this approach requires a high level of coordination between hospitals, outpatient infusion facilities, and multidisciplinary coordination between clinicians, nurses, billing staff, and case management 7 . However, there are several barriers intrinsic to OPAT that compromise its safety and efficacy, thereby preventing the use of OPAT as a transition strategy.…”
Section: Barriers To Traditional Transition Strategiesmentioning
confidence: 99%
“…However, the remainder estimated that in an average week, 19.2% of pharmacists dedicated no time, 26.8% dedicated minimal time (<4 hours), 21.8% dedicated moderate time (4-20 hours), and 11.7% dedicated considerable time (>20 hours) on OPAT patients. 11 These surveys have limitations, because they only survey one physician member of the OPAT team, which could bias responses to the true involvement of ID pharmacists. While relatively small, initial studies involving the inclusion of a pharmacist in the OPAT team have found an improvement in adherence to guideline-based practice (35.9% without an ID-trained pharmacist vs 100% with ID-trained pharmacist), implemented interventions for safety (implemented in 56.1% of patients) and efficacy (interventions in 28.6% of patients), decreased cost (direct cost decrease of $659/patient), and a potential decrease in 30 day readmissions (14.7% with ID-trained pharmacist vs 38.2% without ID-trained pharmacist).…”
Section: Statement Of Needmentioning
confidence: 99%
“…Almost 20% of respondents did not know the answer to this question. However, the remainder estimated that in an average week, 19.2% of pharmacists dedicated no time, 26.8% dedicated minimal time (<4 hours), 21.8% dedicated moderate time (4‐20 hours), and 11.7% dedicated considerable time (>20 hours) on OPAT patients 11 . These surveys have limitations, because they only survey one physician member of the OPAT team, which could bias responses to the true involvement of ID pharmacists.…”
Section: Statement Of Needmentioning
confidence: 99%
“…Overall, these responses were summarized by a lack of institutional support for this modality of therapy. 13 However, research regarding the challenges related to this new modality of therapy is still minimal.…”
mentioning
confidence: 99%